Priming word order by thematic roles: no evidence for an additional involvement of phrase structure - Pappert, Sandra; Pechmann, Thomas (Quarterly journal of experimental psychology, 2014)
Three experiments are reported that studied the priming of word order in German. Experiment 1 demonstrated priming of the order of case-marked verb arguments. However, order of noun phrases and order of thematic roles were confounded. In Experiment 2, we therefore aimed at disentangling the impact of these two possible factors. By using primes that differed from targets in phrase structure but were parallel with regard to the order of thematic roles, we nevertheless found priming demonstrating the critical impact of thematic roles. Experiment 3 replicated the priming effects from Experiments 1 and 2 within participants and revealed no evidence for a modulation of priming by phrase structure. Consequently, our findings suggest that word order priming crucially depends on the structural outline of thematic roles rather than on the linearization of phrases.